SEREX identification of new tumor antigens linked to melanoma-associated retinopathy - Hartmann, Tanja B.; Bazhin, Alexandr V.; Schadendorf, Dirk; Eichmüller, Stefan B. (International journal of cancer, 2005)
Metastatic melanoma still has a very poor prognosis since it withstands conventional therapies like surgery or chemotherapy. A paraneoplastic autoimmune manifestation of this disease is melanoma-associated retinopathy (MAR). MAR has been associated with prolonged survival and may be an early marker of tumor progression. By screening a retina and a melanoma cDNA phage library by SEREX using sera of patients suffering from melanoma and, in some cases, clinical symptoms of MAR, we identified 20 new antigens (HD-MM-28-47), of which 14 clones had high homology to well-known genes. Six of these genes had previously been associated with retina: rhodopsin, visual arrestin, MEK1, SRPX, BBS1 and galectin-3. Individual clones were recognized by up to 43% of patients' sera, while sera of healthy volunteers were negative except in 2 cases. The expression profile of the antigens identified on the basis of homologous EST database entries in healthy tissues was ubiquitous to differential. Using RT-PCR, we found frequent expression of preselected antigens in melanoma cell lines. For rhodopsin, this could be quantified by quantitative PCR. Retinal proteins were recognized by serum antibodies of melanoma patients but not healthy controls. The role of these antigens in MAR awaits further investigation. (Supplementary material for this article can be found on the International Journal of Cancer website at http://www.interscience.wiley.com/jpages/0020-7136/suppmat/index.html.) © 2004 Wiley-Liss, Inc.
First published: 02 November 2004
Gesehen am 10.12.2020